The impact of some internal determinants on bank profitability An applied study on a sample of commercial banks registered in the Iraq Stock Exchange for the period (2005-2017) - Saadon Arabi, Aya (Academic Journal of Nawroz University, 2023)
The research aim is to recognize the effect of some bank profitability determinants, and the main hypothesis is that the determinants have a significant and positive effect on bank profitability. The research relied on the Return on Equity ratio to measure the bank profitability and growth averages of the dependent variables historical data of the banks used as sample of the research, which are (11) banks in the period (2005 -2017), using Panel Data model to recognize the effective relationship between the variables according to EViews 10 program, the research concluded a group of conclusions the most important of them there is a direct correlation relationship between the dependent variables which are (cash credit size, deposits size, and bank size) and the independent variable which is (bank profitability), the research also represented some suggestions mainly, the commercial banks need to achieve the optimum usage of its deposits by investing them in fields that provide more profit than the profit paid to the depositors. Key words: cash credit size, deposits size, bank size, bank profitability, panel data model.